Synthesis and characterization of mixed ligand complexes containing curcumin and 4-aminoantipyrine With some metal ions and study their biological activity (Journal of the College of Basic Education, 2022)
The research includes the preparation and identification of mixed ligand complexes containing curcumin and 4-aminoantipyrine, where the ligandins were added directly to the metal salts in a ratio of (1:1:1) (ligand: ligand: metal). The prepared complexes were identified using physical and spectroscopic methods (FT). -IR, UV, TGA, MS, CHNS) and determination of chlorine content and determination of metal percentage in addition to measurements of molar conductivity and magnetic sensitivity. (Cl] H2O. The biological activity of the prepared ligands and complexes was tested against two types of bacteria (Escherichia Coli) and (Bacillus pumilus). The results showed that the prepared compounds had an activity against bacteria.